Pemberdayaan Pelaku Usaha Melalui Pengelolaan Usaha Wisata Di Desa Warnasari Kecamatan Pangalengan Kabupaten Bandung - Siti Patimah; Trisa Nur Kania; Latifah Adnani; Maun Jamaludin (Universitas Serang Raya, 2020)
Warnasari Village is one of the villages that has a lot of potential including tourist attractions namely Situ Cileunca. Some complaints were obtained by the local community that tourism development was more managed by outside investors or what they called city people. They complained about the condition, where Situ Cileunca was part of their lives but they never felt they owned it. The purpose of activities is to increase understanding related to tourism potential and business management. The method of the activity carried out is training. As a result of the training activities, most of them did not understand how business management, especially marketing and HR management. Participants who participated in the Activity were 20 participants with different types of businesses. But they were very enthusiastic about participating in the training activities.Suggestions, people should be able to increase the desire to try. Besides that there is also a need for motivation so that it can increase business for the surrounding community.